2005
DOI: 10.1002/ffj.1500
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils of the AmazonGuatteria andGuatteriopsis species

Abstract: The essential oils of Guatteria juruensis, G. microcalyx, G. poeppigiana and Guatteriopsis blepharophylla were obtained by hydrodistillation and analysed by GC and GC/MS. The main compounds found in the leaf oil of Guatteria juruensis were spathulenol (77.5%) and α α α α α-pinene (4.5%). The leaf oil of Guatteria microcalyx was dominated by caryophyllene oxide (44.2%), α α α α α-pinene (11.9%) and β β β β β-pinene (6.3%). The major constituents identified in the leaf oil of Guatteria poeppigiana were spathulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 8 publications
2
23
0
2
Order By: Relevance
“…The close affinity between the genera of the Guatteria group has been suggested by many authors after Fries (1939Fries ( , 1943Fries ( , 1959 on the basis of leaf anatomy ( van Setten & Koek-Noorman, 1986), flower anatomy (van Heusden, 1992), fruit and seed morphology (van Setten & KoekNoorman, 1992), unusual chromosome differentiation and cuticular folding patterns (Morawetz & Waha, 1985), a distinct pollen type (Walker, 1971;Morawetz & Waha, 1985), and oil composition analysis (Maia & al., 2005). This close affinity was corroborated in a phylogenetic study based on rbcL sequences (Bygrave, 2000).…”
Section: Introductionmentioning
confidence: 75%
“…The close affinity between the genera of the Guatteria group has been suggested by many authors after Fries (1939Fries ( , 1943Fries ( , 1959 on the basis of leaf anatomy ( van Setten & Koek-Noorman, 1986), flower anatomy (van Heusden, 1992), fruit and seed morphology (van Setten & KoekNoorman, 1992), unusual chromosome differentiation and cuticular folding patterns (Morawetz & Waha, 1985), a distinct pollen type (Walker, 1971;Morawetz & Waha, 1985), and oil composition analysis (Maia & al., 2005). This close affinity was corroborated in a phylogenetic study based on rbcL sequences (Bygrave, 2000).…”
Section: Introductionmentioning
confidence: 75%
“…[19][20][21][22] Among these identified components, the oxygenated sesquiterpene spathulenol is considered as a chemotaxonomic marker of species of Annonaceae, because it has been identified in several species of this family belonging to the genera Annona, Artabotrys, Cleistopholis, Desmos, Duguetia, Fusae, Goniothalamus, Guatteria, Guatteriopsis, Hexalobus, Melodorum, Pachypodanthium, Piptostigma, Uvaria and Xylopia. 12,[19][20][21][22] (E)-caryophyllene is frequently found in the species of Annona, and could be considered together with caryophyllene oxide as chemotaxonomic markers for this genus. 12,[19][20][21][22] …”
Section: Cultures Of Leishmania Amazonensismentioning
confidence: 99%
“…12,[19][20][21][22] (E)-caryophyllene is frequently found in the species of Annona, and could be considered together with caryophyllene oxide as chemotaxonomic markers for this genus. 12,[19][20][21][22] …”
Section: Cultures Of Leishmania Amazonensismentioning
confidence: 99%
“…(Fig. 1) (Morawetz & Waha 1985), a distinct pollen type (Walker 1971;Morawetz & Waha 1985), oil composition analysis (Maia et al 2005), and wood anatomy ). These studies suggested a close affinity of the four genera but did not determine their phylogenetic relationships with respect to each other.…”
Section: Introductionmentioning
confidence: 99%